THE ACCOUNTING INFORMATION QUALITY UNDER THE INTERNATIONAL FINANCIAL REPORTING STANDARDS AND COMPANIES' FINANCIAL PERFORMANCE - Dr. Ammar Abdulqader Salih (Scholar Express Journals, 2024)
The application of the international financial reporting standards is no longer a luxury because of the international context which is characterized by the dismantling of the economic barriers, the monetary operations' globalization and financial movements liquidity, but in fact, it has become an increasingly continuous necessity for the producing entities at the local and global levels. In this context, the primary goal of IFRS aims to provide a useful accounting and financial information for making investment and credit decisions. Thus, this research and by using the statistical analysis on the SPSS program, aims to highlight and evaluate the correlation that exists between the quality of provided accounting information in accordance with the international financial reporting standards and financial performance (in the short and medium term) for the companies that announce prepared brief accounting statements in accordance with the International Financial Reporting Standards. This quantitative study, which uses a Likert-type questionnaire rated from 1 to 5, and according to the responses collected from a sample of (74) individuals (the sample that covers the executive managers and accountants in the institutions, besides the professors and doctoral students for the international financial reporting standards) with the aim of proving and statistically verifying the correlation and interconnectedness between the qualitative characteristics of an accounting information and entities' financial performance. The results obtained from the data analysis software showed that there is a presence of a negative correlation sign “in the short term” between the components of the distinct variables and a positive correlation between the same variables “in the medium and long term”. The positive result of the correlation between the prepared accounting information quality in accordance with the international financial reporting standards and financial performance in the medium and long term, with the expectation that it will be confirmed later through a confirmatory study, may be a motivating factor that encourages companies to adopt the international accounting standards despite the costs that are incurred by this transformation
Keywords: return; risk; investment portfolio; Iraq Stock Exchange